THE INFLUENCE OF USING HANGAROO GAME TOWARDS STUDENTS’ VOCABULARY MASTERY - Eva Faliyanti; Evi Puspita Sari (Intensive Journal, 2018)
The method is held through quantitative research. The researcher uses quasi- experimental research. The research is conducted in the fourth semester of English Department of Muhammadiyah University of Metro in academic year 2016/2017. The population in this research population is all students at the fourth semester of English Department. It consisted one class and the class consisting of 38 students. The researcher takes one class to be divided into two classes as a sample. They were experimental class and control class. The objective of this research is to know whether there is the positive and significant influence of using Hangaroo game toward students’ vocabulary mastery. To analyze data the researcher uses T- test formula. The researcher got the result of tratio  is 3,55 and ttable is 2,42 it means that tratio>ttable. Then, the criteria of Ttest is Ha accepted if tratio>ttable. So there is the positive and significant effect of Hangaroo game toward students’ vocabulary mastery at the fourth semester of English Department of Muhammadiyah University of Metro in academic year 2016/2017.